Asylum Seekers and Refugee Management: (Im)Balance Burden Sharing Case between Indonesia and Australia - Arie Afriansyah; Hadi Rahmat Purnama; Akbar Kurnia Putra (Faculty of Law, Sriwijaya University, Indonesia, 2022)
Since the 1970s, Indonesia has been acting as a transit country for asylum seekers and refugees to reach Australia and New Zealand. Being a non-state party to the Refugee Convention, Indonesia has become the strategic partner for Australia in managing the issue of asylum seekers and refugees. The two countries have been involved in many bilateral and regional arrangements to tackle the issues. The “Bali process” is one of Indonesia and Australia's arrangements to lead the region in tackling forced migration and refugees. Unfortunately, despite their “common” interests, many of Australia's policies towards asylum seekers have negatively impacted Indonesia in many ways. This paper uses desk study research with a normative approach to analyse nationally and internationally relevant laws and policies. This paper analyses the Bali Process as regional cooperation means of burden-sharing in which Indonesia and Australia play dominant roles while scrutinising how both countries implement the policies within their domestic realms. In addition, the dynamics within the two countries will also be examined to understand how they shape their policies. This paper argues that Indonesia has fulfilled its part by managing these protected persons within Indonesia. However, Australia seems to consistently try to shift its burden to Indonesia as its neighbouring state. By revisiting the Bali Process arrangement, it is suggested that Australia needs to respect its commitment and take any means necessary to keep good relations with its neighbours, including Indonesia.